Nature of science: bats and frogs and midges, oh my!. (2nd October 2019) - Gutierrez, Stephanie; Rubin, Emily; Inskeep, David; Bernal, Ximena E.
Abstract: Understanding the nature of science has long been a focus of science education reform efforts, including the Next Generation of Science Standards. Students' views about the process of how scientific knowledge is acquired has been shown to affect their ability to learn scientific concepts. Integrating the nature of science into science lesson plans allows students to connect how scientists learned the information they are currently learning. Lesson plans that incorporate the nature of science should provide students with the opportunity to explore their own ideas and develop their own conclusions with support from their teacher. Here we provide a lesson plan that facilitates the instruction of the nature of science and clearly identifies the specific NGSS expectations addressed with the goal of improving student learning. In particular, we lay out a guide to implement on-going ecological research in activities to improve NOS understanding based on a constructivist approach to learning.